Enhancing historical heritage and religious tourism in the North of Portugal: the monasteries route - Liberato, Pedro (2022)
The creation of cultural and tourism routes and itineraries are important resources, which allow the enhancement and dynamization of destinations, particularly from an economic perspective, by increasing tourism demand. As such, it is a differentiating and unique product, offered to visitors and tourists, and that has observed a considerable demand. Although the dimension of religious and cultural tourism is widely studied by several authors, the tourist and cultural routes and itineraries to boost and enhance the historical and cultural heritage are not sufficiently studied, so the aim of this paper is to extend the scientific knowledge on this topic. The general objective of this research is to evaluate the role of Portugal’s historical and cultural heritage in the context of the creation of the monasteries route, focusing on Northern Portugal. The method applied in this research was the qualitative methodology, with data being collected through semi-structured interviews. Ten interviews were applied to the representatives of several entities. According to the exhaustive and detailed analysis of the information and data provided, it can be proven that UNESCO’s attribution of the World Heritage designation to destinations and sites gives them greater recognition and an exponential increase in tourists; the historical and cultural heritage is one of the main factors for the choice of a destination; the historical and cultural heritage is positively leveraged by public and governmental entities; the role of pilgrimages positively influences the increase of the tourism sector in Portugal bringing several advantages mainly in the hotel and restaurant sector; the creation of a tourism and cultural itinerary fosters knowledge, the preservation of the historical and cultural legacy and, finally, repercussions in the economy of Portugal; convents and monasteries are one of the dimensions that are targeted by national policies of preservation of the historical and cultural heritage.